Shigella host: Pathogen interactions: Keeping bacteria in the loop. (2nd July 2019) - Liu, Guangyu; Pilla, Giulia; Tang, Christoph M.
Abstract: Shigella spp. are Gram‐negative enteric pathogens and the leading cause of bacterial dysentery worldwide. Since the discovery more than three decades ago that the large virulence plasmid of Shigella is essential for pathogenesis, our understanding of how the bacterium orchestrates inflammation and tissue destruction at the mucosal surface has been informed by studies employing the rabbit ileal loop model. Here, we outline how Phillippe Sansonetti, together with his co‐workers and collaborators, exploited this model to provide a holistic view of how Shigella survives in the intestinal tract, traverses the intestinal epithelial barrier, and manipulates the host immune system to cause disease.